The Enlightenment. (ABC-CLIO, 2008)
One of the few self-named historical movements, the Enlightenment in 18th-Century Europe was a powerful intellectual reaction to the dominance of absolutist monarchies and religious authorities. Building upon the discoveries of the Scientific Revolution, Enlightenment thinkers--philosophes--set out to improve humanity through reason, knowledge, and experience of the natural world rather than religious doctrine or moral absolutes. Their emphasis on truth through observable phenomena set the standard of thought for the modern age, deeply influencing the areas of government, the modern state, science, technology, religious tolerance and social structure. The Enlightenment's legacy is particularly visible in the United States, where its ideals inspired a revolution and served as the building blocks for the Declaration of Independence and the American Constitution. Narrative chapters, photos, biographical sketches, primary document excerpts, and an extensive bibliography expand the readers' understanding of the event, providing a current perspective on this key turning point in Western ideology. Comprehensive narrative chapters explore the historical background of the movement, as well as its relationship to nature and natural philosophy, religious belief and church institutions, society and the state, and the French Revolution. Photos, biographical sketches of key figures, excerpts from important primary documents of the time, and an extensive bibliography expand the reader's understanding of the movement that ushered in the modern era.